Modelling responses of the inert-gas washout and MRI to bronchoconstriction - Foy, B; Kay, D; Bordas, R (Elsevier, 2016)
Many lung diseases lead to an increase in ventilation heterogeneity (VH). Two clinical practices for the measurement of patient VH are in vivo imaging, and the inert gas multiple breath washout (MBW). In this study computational modelling was used to compare the responses of MBW indices LCI and scond and MRI measured global and local ventilation indices, σr and σlocal, to constriction of airways in the conducting zone of the lungs. The simulations show that scond, LCI and σr behave quite similarly to each other, all being sensitive to increases in the severity of constriction, while exhibiting little sensitivity to the depth at which constriction occurs. In contrast, the local MRI index σlocal shows strong sensitivity to depth of constriction, but lowered sensitivity to constriction severity. We finish with an analysis of the sensitivity of MRI indices to grid sizes, showing that results should be interpreted with reference to the image resolution. Overall we conclude that the application of both local and global VH measures may help to classify different types of bronchoconstriction.